Perspective of University Students from Different Programs at Universidad Nacional (Costa Rica) regarding Democracy in the Family, Educational Institutions, and the Country - María Esther Morales-Ramírez; Marianella Castro-Pérez; Marianela Bolaños-Mora (Universidad Nacional, Costa Rica, 2015)
This article focuses on democracy and is aimed at analyzing the perspective of university students from Universidad Nacional de Costa Rica (UNA) regarding democracy in the family, educational institutions as well as the country in general.  Research was conducted based on a questionnaire administered to 138 students from different programs and levels at Universidad Nacional de Costa Rica.  This research constitutes an input for parents, teachers and educational institution authorities to reflect on whether the dynamics in which they operate in their respective contexts foster the introduction and implementation of democratic values.  It was generally concluded that there is an overall feeling of dissatisfaction and frustration experienced by the population, due to the way the different administrations have ruled the country in recent years and, consequently, towards the prevailing democratic system. In addition, the population has become more suspicious and reluctant to exercise their right to vote and actively participate in the process.  Consequently, for the society to be truly democratic, families should promote assertive communication based on understanding, respect, fairness, freedom, affection, participation, equality and collaboration.  It is appealing to think that all of this will contribute to a harmonious and peaceful coexistence and to the formation and strengthening of civic and democratic values that lead to genuine citizen participation, starting from early childhood in schools and moving to higher levels.